Impacts of attitudes, social development, mother’s educational level and self-efficacy on academic achievement in mathematics - Zamora-Araya, José Andrey (Uniciencia, 2020)
The document addresses the problem of low academic performance in Mathematics (LPM). Its principal objective is to analyze how academic performance relates to attitudes towards this subject, perceptions of self-efficacy, social development and the educational level of students’ mothers. One hundred and ninety-seven (197) students in the 7th, 8th and 9th grades of middle and high school, between 13 and 16 years old, participated in the study. This correlational study used techniques of exploratory factor analysis and multiple regression to determine the association between the constructs. The results confirm the importance of students trusting in their abilities when performing mathematical tasks, which is reflected on the significant coefficients for the dimensions of confidence (p = 0.001) and master experience (p <0.001), but the educational level of the mother did not have a significant effect on learning outcomes. Unexpected results were also found with respect to social development and some dimensions of the scale of attitudes towards mathematics, but the impacts of these constructs and self-efficacy on LPM were verified. Based on these findings, it is recommended to carry out further research on the effects of these factors.